Andrographolide exerted anti-inflammatory effects thereby reducing sex hormone synthesis in LPS-induced female rats, but had no effect on hormone production in healthy ones - Yuan, Xiaoyan; Xu, Wenhao; Yan, Zijun; Xu, Xingmeng; Chen, Yanqing; Chen, Simin; Wang, Ping (Frontiers in Pharmacology, 2022)
Females have higher inflammatory tolerance because they have some special sex-related anti-inflammatory pathways. Andrographolide, a diterpene lactone compound from Andrographis paniculata (Burm.f.) Nees, has a powerful anti-inflammatory effect. But whether andrographolide regulates sex-related anti-inflammatory pathways in females has yet to be reported. A non-targeted metabonomics method was employed to investigate the metabolic pathways of andrographolide in LPS-induced inflammatory female rats. Substances and genes were then selected out of gender-related pathways discovered by metabonomics experiments and their quantities or expressions were evaluated. Furthermore, the effects of andrographolide on these chemicals or genes in non-inflammatory female rats were also examined in order to investigate the cascade interaction between anti-inflammatory mechanisms and metabolites. The biomarkers of 24 metabolites in plasma were identified. Following pathway enrichment analysis, these metabolic markers were clustered into glycerophosphate, glycerolipids, inositol phosphate and steroid hormone synthesis pathways. Validation experiments confirmed that andrographolide lowered post-inflammatory female sex hormones such as progesterone, estradiol, corticosterone, and testosterone rather than increasing them. Andrographolide may have these effects via inhibiting the overexpression of CYP11a1 and StAR. However, andrographolide had no effect on the expression of these two genes or the four types of hormones in non-inflamed female rats. Similarly, andrographolide decreased TNF-α, IL-6 and IL-1β production in inflammatory rats but showed no effect on these inflammatory markers in non-inflammatory rats. LPS and other inflammatory cytokines promote hormone production,which in turn will prevent increased inflammation. Therefore, it may be hypothesized that andrographolide's reduction of inflammatory cytokine is what generates its inhibitory action on sex hormones during inflammation. By blocking the activation of inflammatory pathways, andrographolide prevented the stimulation of inflammatory factors on the production of sex hormones. It does not, however, directly inhibit or enhance the synthesis of sex hormones.